Further Observations in Cerebro-Costo-Mandibular Syndrome: Exploration with CT Imaging - Bhat, Venkatraman; Belval, Vinay; Kumar, Santhosh; Auti, Onkar (Journal of Child Science, 2020)
Cerebro-costo-mandibular syndrome (CCMS) is a rare syndrome characterized by posterior rib ossification gaps and orofacial anomalies. Posterior rib ossification gaps are the hallmark of the disease and mimic multiple old rib fractures. The condition is caused by heterogeneous mutation of Small Nuclear Ribonucleoprotein Polypeptides B and B1 (SNRPB) gene on the chromosome 20p13. There is scanty literature regarding the extent of bony changes and the associated pulmonary-airway abnormalities on computed tomography (CT) imaging. In this case report, we presented a detailed CT imaging features of a case of CCMS in a male infant. This report highlighted on the nature of osseous defects, structural changes in the chest wall, airways, lungs, and a wide range of spinal anomalies. Some of our observations regarding the changes in the airway and chest wall are likely to have bearing on evaluating the prognosis and the need for respiratory support.
Keywords: cerebro-costo-mandibular syndrome; posterior rib ossification gaps; CT imaging